The evil that men do - Gleason, Robert (Robert Herman) (Forge, 2018)
Income inequality and the offshore hoarding of illicit black funds have reached such extremes that the earth's democracies are in peril. The oligarchs are taking over. The People worldwide, however, are rising up, and they demand that the UN seize and redistribute all that illegal filthy lucre. But it will not be easy. The world's oligarchs will not go gentle. Mikhail Putilov, Russia's strongman; J. T. Tower, the American president, and Wahid al-Waheed, the Saudi Ambassador to the US will do anything to stop and destroy this global expropriation moment--even if it means nuking the UN.